Establecimiento de tres medios de cultivo para la fase de enraizamiento in vitro de anturio anthurium andreanum - Lucero Murillo, Jessenia Del Rocío (2013)
Establishment of three cultivation means for the phase of rootment in anturio vitro (Anthurium andreanum) he was carried out in the Laboratory of Biotechnology of the Ability of Agricultural Sciences, and you outlines the following objectives: 1. to determine the good concentration of auxinas, by means of the evaluation of three cultivation means in the rootment phase that allows the formation of more number of roots in the explantes; 2. to establish the effect of the auxinas in the rootmentof the anturios plants (Anthurium andreanum Lind). you employment the means Murashige & Skoog adjusting the pH at 4,8 and sterilized in a key car to 120º C during 30 minutes, for this rehearsal buds of the multiplication stage were chosen that they had 2 cm of the height and it was sowed in glass flasks with 20 ml of half. Level them they were placed in an incubation room, to a temperature of 27º C, and relative humidity of 80%. The treatments four levels of the auxinas ANA, AIA and ANA+AIA 0,5-1,5-2,5 and 3,5 consisted; with two concentrations of salts 50 and 100 mg, in which it was evaluated height of the plant, number of leaves, number of roots, longitude of the roots, percentage of contamination, percentage of survival. In the number of leaves for plant stood out the treatments formulated with AIA 0, 5 + you leave. The means of cultivation with which you/they were obtained bigger number roots was ELL 1, 5 + 50% of concentration of salts, I also stimulate the lengthening radicular, favoring this way the absorption of nutritious. For the group of treatments with AIA 40% of plants emitted roots; the level of lower rootment was obtained with ANA mixture + AIA, due to a probable antagonistic effect, AIA and ANA is hormones of the group of the auxinas, ANA was more favorable for the formation of roots of the buds and AIA for the emission to foliate of the same ones. The means of cultivation recommended for the enraizamiento in anturio vitro is ANA 1,5 mg. and 50% of concentration of salts. The techniques in vitro are favorable for the propagation of plants and at the same time susceptible to the contamination for agents patógenos if it is not taken the adapted conditions of asepsis.